A Comparison of the Medium-term Impact and Recovery of the Pakistan Floods and the Haiti Earthquake: Objective and Subjective Measures. Issue 3 (29th May 2014) - Weiss, William M.; Kirsch, Thomas D.; Doocy, Shannon; Perrin, Paul
Abstract Introduction The 2010 Haiti earthquake and Pakistan floods were similar in their massive human impact. Although the specific events were very different, the humanitarian response to disasters is supposed to achieve the same ends. This paper contrasts the disaster effects and aims to contrast the medium-term response. Methods In January 2011, similarly structured population-based surveys were carried out in the most affected areas using stratified cluster designs (80×20 in Pakistan and 60×20 in Haiti) with probability proportional to size sampling. Results Displacement persisted in Haiti and Pakistan at 53% and 39% of households, respectively. In Pakistan, 95% of households reported damage to their homes and loss of income or livelihoods, and in Haiti, the rates were 93% and 85%, respectively. Frequency of displacement, and income or livelihood loss, were significantly higher in Pakistan, whereas disaster-related deaths or injuries were significantly more prevalent in Haiti. Conclusion Given the rise in disaster frequency and costs, and the volatility of humanitarian funding streams as a result of the recent global financial crisis, it is increasingly important to measure the impact of humanitarian response against the goal of a return to normalcy. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>WM</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Weiss</surname> </string-name>, <string-name><given-names>TD</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Kirsch</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Doocy</surname></string-name>, <string-name><given-names>P</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Perrin</surname></string-name>. A comparison of the medium-term impact and recovery of the Pakistan floods and the Haiti earthquake: objective and subjective measures . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>3</issue>):<fpage>1</fpage>-<lpage>8</lpage>.</mixed-citation>